Preparation of zinc oxide nano- and micro-structures using hydrothermal-template method and their applications - Ramimoghadam, Donya (2014)
Pure zinc oxide (ZnO) was successfully synthesized using various non bio- and biotemplates namely, sodium dodecyl sulfate (SDS), cetyl trimethylammonium bromide (CTAB), palm olein (PO), uncooked- and cooked rice. ZnO nano- and microstructures were synthesized through hydrothermal method. The physicochemical properties of the resulting samples were characterized for samples synthesized at various amount of templates to zinc precursor. Different morphologies such as flower-, rod-, flake-, sphere-rose-, triangular- and star-like shapes were obtained. Moreover, an enhancement in BET surface area and modification in pore texture were also observed. This modification resulted from either increasing the pore size and volume or the uniformity of the pores. However, optical properties like UV-Vis absorption and band gap energy are generally quite similar to that of ZnO synthesized without templating agents. Last but not least, we also investigated the effect of the addition of the as synthesized ZnO nanoparticles into polysulfone/zinc oxide mixed matrix membranes (PSf-MMMs) for the application of gas separation. The results indicated an improvement in CO2/CH4 separation and permeance properties of PSf/ZnO MMMs.